Monitoring of Federal Criminal Sentences, (United States), 2002 ([Verlag nicht ermittelbar], 2004)
This collection contains information on federal criminal cases sentenced under the Sentencing Guidelines and Policy Statements of the Sentencing Reform Act of 1984. The data files include all cases received by the United States Sentencing Commission that had sentencing dates between October 1, 2001, and September 30, 2002, and were assessed as constitutional. Constitutionality compares each case's sentencing date, circuit, district, and judge to provide uniformity in reporting the cases. In 1999, the United States Sentencing Commission added more variables from its databases to this collection, so the data are now provided in two files. Part 1, Main Data File, includes the most important variables for each case, such as defendant's age, criminal history points, armed criminal status, case disposition, sentence, and fines applied. Part 2, Supplemental Data File, contains additional variables involving multiple guideline computation and count-based statutes. For a more detailed discussion of the two files, users should consult the codebook.